2008
DOI: 10.4161/rna.7116
|View full text |Cite
|
Sign up to set email alerts
|

Over-represented sequences located on 3' UTRs are potentially involved in regulatory functions

Abstract: Eukaryotic gene expression must be coordinated for the proper functioning of biological processes. This coordination can be achieved both at the transcriptional and post-transcriptional levels. In both cases, regulatory sequences placed at either promoter regions or on UTRs function as markers recognized by regulators that can then activate or repress different groups of genes according to necessity. While regulatory sequences involved in transcription are quite well documented, there is a lack of information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…So, besides poly(A) signals, 25% of the remaining regulatory elements are AREs or CPEs. A separate in silico study by Yoon et al showed a large portion of over-represented sequences located in 3′UTRs contain the sequence motifs AUUUA and UAUUUAU, the two basic core sequences of AREs ( 66 ). A separate study conducted by Robins et al showed ∼75% of miRNA targets are in the AU-rich 3′UTR population and genes with AU-rich 3′UTRs are preferentially associated with transcription and translation events ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, besides poly(A) signals, 25% of the remaining regulatory elements are AREs or CPEs. A separate in silico study by Yoon et al showed a large portion of over-represented sequences located in 3′UTRs contain the sequence motifs AUUUA and UAUUUAU, the two basic core sequences of AREs ( 66 ). A separate study conducted by Robins et al showed ∼75% of miRNA targets are in the AU-rich 3′UTR population and genes with AU-rich 3′UTRs are preferentially associated with transcription and translation events ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…These sequences often overall with or include binding sites for HuR, TIA-1, and consist of AU rich elements (ARE) and GU rich elements (GRE). A significant portion of these have the core ARE sequences AUUUA and UAUUUAU ( 33 ). It is therefore of interest to determine whether or not specific sequence motifs in a given 3′UTR influence miRNA functional repression of that message.…”
Section: Introductionmentioning
confidence: 99%
“…We searched a dataset of 20,840 validated 3Ј-UTR sequences of human transcripts (37) and identified ϳ8,000 transcripts containing at least one putative Msi1 binding site. It is FIGURE 1.…”
Section: Rip-chip Analysis Of Msi1 and Identification Of Preferentiallymentioning
confidence: 99%
“…This is a functional unit in which multiple physiologically related transcripts can be co-ordinately regulated during splicing, export, stability, localization, and translation. These subpopulations of mRNAs bind the same RBPs in a dynamic manner because each mRNA can join different RNA operons [20][21][22][23] . Some of us recently reported an example of RNA operon for human major histocompatibility complex II gene 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the regulatory function of the 3′ UTR sequences 21 , we identified a cluster of 21 human genes comprising PON2 characterized by the sharing at the 3′ UTR leader of the conserved sequence: UUUC-CUUAAAAU 21,26 (Supplementary Table 6). We hypothesized a post-transcriptional control of PON2 via an mRNA operon relying upon RBPs recognizing the conserved sequence.…”
Section: Introductionmentioning
confidence: 99%